Question

Asked By CosmicGlider20 at

Answered By Expert

Felix

Expert · 4.3k answers · 4k people helped

Solution By Steps

Step 1: Differentiate each term

To find

\frac{d y}{d x}, we need to differentiate

y = e^{\sqrt{x}} + e^{-\sqrt{x}} with respect to

x.

Step 2: Apply the chain rule

For

e^{\sqrt{x}}, let

u = \sqrt{x}, then

\frac{d}{dx} e^{\sqrt{x}} = e^{\sqrt{x}} \cdot \frac{d}{dx} \sqrt{x} = e^{\sqrt{x}} \cdot \frac{1}{2\sqrt{x}}.

For

e^{-\sqrt{x}}, let

u = -\sqrt{x}, then

\frac{d}{dx} e^{-\sqrt{x}} = e^{-\sqrt{x}} \cdot \frac{d}{dx} (-\sqrt{x}) = e^{-\sqrt{x}} \cdot \left(-\frac{1}{2\sqrt{x}}\right).

Step 3: Combine the results

Combining the derivatives, we get:

\frac{d y}{d x} = \frac{e^{\sqrt{x}}}{2\sqrt{x}} - \frac{e^{-\sqrt{x}}}{2\sqrt{x}} = \frac{e^{\sqrt{x}} - e^{-\sqrt{x}}}{2\sqrt{x}}

Final Answer

The derivative of

y = e^{\sqrt{x}} + e^{-\sqrt{x}} with respect to

x is:

\boxed{A}

🧑🏫 More Questions

👉 Interested in exploring further?

Chrome Extension

1. Search answers from our 90+ million questions database.

2. Get instantly AI Solutions powered by most advanced models like GPT-4, Bard, Math GPT, etc.

3. Enjoy one-stop access to millions of textbook solutions.

4. Chat with 50+ AI study mates to get personalized course studies.

5. Ask your questions simply with texts or screenshots everywhere.